2007
DOI: 10.1111/j.1440-1819.2007.01610.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and lipid metabolism of long‐term risperidone monotherapy in patients with schizophrenia

Abstract: Risperidone has a relatively low risk of causing obesity and diabetes mellitus and is a first-line treatment for schizophrenia. The aim of the present study was to investigate glucose and lipid metabolism, and feeding-control parameters in schizophrenia patients treated with long-term risperidone monotherapy. Fifteen patients with paranoid-type schizophrenia who had been treated with risperidone and had Global Assessment of Function (GAF) scores >70 were selected and compared with healthy volunteers (n = 25). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 33 publications
0
39
2
Order By: Relevance
“…Furthermore, the majority of longer-term studies reporting on ghrelin levels after more than 6 months of SGA treatments showed an upregulation effect of SGAs on circulating total (Esen-Danaci et al, 2008;Murashita et al, 2007a;Murashita et al, 2005), active (Murashita et al, 2007a;Murashita et al, 2005;Palik et al, 2005) or desacyl (Perez-Iglesias et al, 2008) ghrelin levels, with the exception of two studies (Chen et al, 2011;Kim et al, 2008) (see details in Table 1). Interestingly, both of these two studies reported on total ghrelin levels only (Chen et al, 2011;Kim et al, 2008); while the three long-term studies reported on active ghrelin levels all indicated that SGAs can increase ghrelin levels (Murashita et al, 2007a;Murashita et al, 2005;Palik et al, 2005). Since acyl ghrelin (noctanoyl ghrelin) is the biologically active form of ghrelin which binds to the GHS-R1a receptor to exert its orexigenic effect (as mentioned earlier in section 2.1), it might be more relevant in the context of SGA-induced body weight gain compared to total ghrelin, although SGAs, as suggested by another study, also increase desacyl (inactive) ghrelin levels in the long-term (Perez-Iglesias et al, 2008).…”
Section: Longer Term Effects Of Sgas On Circulating Ghrelin Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the majority of longer-term studies reporting on ghrelin levels after more than 6 months of SGA treatments showed an upregulation effect of SGAs on circulating total (Esen-Danaci et al, 2008;Murashita et al, 2007a;Murashita et al, 2005), active (Murashita et al, 2007a;Murashita et al, 2005;Palik et al, 2005) or desacyl (Perez-Iglesias et al, 2008) ghrelin levels, with the exception of two studies (Chen et al, 2011;Kim et al, 2008) (see details in Table 1). Interestingly, both of these two studies reported on total ghrelin levels only (Chen et al, 2011;Kim et al, 2008); while the three long-term studies reported on active ghrelin levels all indicated that SGAs can increase ghrelin levels (Murashita et al, 2007a;Murashita et al, 2005;Palik et al, 2005). Since acyl ghrelin (noctanoyl ghrelin) is the biologically active form of ghrelin which binds to the GHS-R1a receptor to exert its orexigenic effect (as mentioned earlier in section 2.1), it might be more relevant in the context of SGA-induced body weight gain compared to total ghrelin, although SGAs, as suggested by another study, also increase desacyl (inactive) ghrelin levels in the long-term (Perez-Iglesias et al, 2008).…”
Section: Longer Term Effects Of Sgas On Circulating Ghrelin Levelsmentioning
confidence: 99%
“…Clinical data has indicated ghrelin production and signalling is upregulated, at least in a subpopulation of patients under SGA treatments (Esen-Danaci et al, 2008;Murashita et al, 2007a;Murashita et al, 2005;Palik et al, 2005;Perez-Iglesias et al, 2008), which was supported by the majority of acute and chronic animal studies (Murashita et al, 2007b;van der Zwaal et al, 2012;Weston-Green et al, 2011). Although ghrelin signalling is only indirectly related to SGAs, and therefore other mechanisms (for example, antagonism of H1, H3, 5-HT2a, M3 receptors) cannot be excluded, the majority of data as discussed above indicate that the altered ghrelin signalling under SGA treatments can at least partly explain the weight gain sideeffects induced by SGAs.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another human vitro study with 7-day olanzapine exposure had no effect on adiponectin (Murashita et al, 2005) 7 olanzapine Prospective 6-month study Compared to baseline, no significant change in adiponectin levels although body fat significantly increased at month 6. (Murashita et al, 2007) 15 risperidone 25 controls…”
mentioning
confidence: 99%
“…The effects of atypical antipsychotics, as well as other symptoms of metabolic syndrome, on serum adiponectin levels are increasingly becoming the subject of research. Previous studies investigating the relationship between serum adiponectin levels and the usage of atypical antipsychotics have focused more on short-term effects [9,[13][14][15][16][17]. In this study, our purpose was to investigate the effects of atypical antipsychotic usage on serum adiponectin levels and metabolic parameters based on their association with long-and short-term atypical antipsychotic usage.…”
Section: Introductionmentioning
confidence: 99%